Insecticide Resistance Patterns in Mosquitoes of Public Health Importance in North Carolina, 2018-2023. - Harrison Dunn, Jeffrey; Richards, Stephanie L.; White, Avian; Byrd, Brian D. (Journal of Environmental Health, 2025)
Mosquito insecticide resistance is a global public health issue that must be monitored and addressed at the local level by rotating insecticides with different modes of action. In our study, insecticide resistance was monitored in Aedes albopictus and Culex pipiens/quinquefasciatus in North Carolina during 2018-2023 via Centers for Disease Control and Prevention bottle bioassays. Trends in insecticide resistance were compared by region and year for mosquito control-formulated insecticide products containing the following active ingredients: bifenthrin, deltamethrin, etofenprox, permethrin, malathion, naled, and sumithrin/prallethrin. There was a signifi cant difference (p = .003) in insecticide resistance between the two species, with Culex populations having higher insecticide resistance than Aedes. Bottle bioassays that test active ingredients are a starting point for mosquito control programs, and insecticide resistance testing should be conducted at least annually for local mosquito populations. Further assessments of formulated insecticide products should be carried out for mosquito populations showing resistance to active ingredients, which can inform operational decisions.